1976
DOI: 10.1111/j.1365-2389.1976.tb02010.x
|View full text |Cite
|
Sign up to set email alerts
|

A Toposequence of Alpine Soils on Calcareous Micaschists, Northern Adula Region, Switzerland

Abstract: On calcareous micaschists in the northern Adula Region, Switzerland, brown soils are formed under grasses and herbs at altitudes below 2000 m. Podzols occur below Ericaceae below 2000 m and are formed irrespective of vegetation above this altitude. Calcimorphic soils are not found. Brown soils have a stable clay mineral association of chlorite and mica, while in the A horizons of podzols and in initial podzols alteration of chlorites to smectites occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…These might include chlorite-smectites with XRD peaks at 28 A for the air-dried Mgsaturated state, at 32 ~ for the glycerated state, at between 24 and 28 ~, for K-saturated air-dried samples and at 24 and/or 22 ~ for heated samples. Mica-chlorites, regarded as important phases in some Swiss alpine soils, where they were characterized as non-expanding 24 A phases (Buurmann et al, 1976), could also have escaped recognition in the present soils. The difficulty of drawing clear boundaries between these differentlynamed species and of identifying each of them in a mixture supports Millot's (1970) contention that 'these words are without doubt applied to a reality with more nuances than the rigorous definitions of these words would have us believe' and that 'a succession of several distinct terms, assuming they are appropriate, encompasses a reality which is more nearly continuous'.…”
Section: Identification Of Minerals In a Horizon Samplesmentioning
confidence: 90%
See 3 more Smart Citations
“…These might include chlorite-smectites with XRD peaks at 28 A for the air-dried Mgsaturated state, at 32 ~ for the glycerated state, at between 24 and 28 ~, for K-saturated air-dried samples and at 24 and/or 22 ~ for heated samples. Mica-chlorites, regarded as important phases in some Swiss alpine soils, where they were characterized as non-expanding 24 A phases (Buurmann et al, 1976), could also have escaped recognition in the present soils. The difficulty of drawing clear boundaries between these differentlynamed species and of identifying each of them in a mixture supports Millot's (1970) contention that 'these words are without doubt applied to a reality with more nuances than the rigorous definitions of these words would have us believe' and that 'a succession of several distinct terms, assuming they are appropriate, encompasses a reality which is more nearly continuous'.…”
Section: Identification Of Minerals In a Horizon Samplesmentioning
confidence: 90%
“…Such a phase, which would be trioctahedral, has been reported to form from chlorite on weathering (Loveland & Bullock, 1975;Ross & Kodama, 1976). In addition, a study of Swiss alpine soils formed on schists led Buurmann et al (1976) to conclude that smectites therein had formed from chlorites. Such smectites would be montmorillonitic, according to Buurmann et al, and not beidellitic as were the smectites in, for example, Ross& Mortland's (1966) andCampbell's (1975) Studies, and in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The weathering end products in the Bw and A2 horizons were not beideUite, as has been reported in other studies (Wilson, 1987). Buurman et aL (1976) have shown that smectites that had formed from chlorite in alpine soils were montmoriUonite.…”
Section: Discussionmentioning
confidence: 99%